Experience of Using New Technologies in Retail Trade - A. A. Garnova (Вестник Российского экономического университета имени Г. В. Плеханова)
Lately we can observe serious changes in global retail trade stipulated by the development of technologies and modifications in customer expectations. Accumulation of knowledge of practical nature about use of digital technologies in retain trade has not got sufficient theoretical and methodological understanding so far. The goal of the research is to identify trends in using new technologies in retain trade by generalization of overseas experience. The informational base of the research is formed by works by foreign authors published in data base Scopus and Web Science from 2002 to 2023, press-releases of foreign retain companies and information on sites of trade equipment manufacturers. Certain new technologies were found that exercise considerable impact on retain trade. Overseas experience of introducing new technologies was analyzed and their advantages in view of different aspects of comfort for customers and provision of social presence were identified. Apart from that opportunities were studied that can offer new technologies for improving operational efficiency of retail trade enterprises. A conclusion was made that they are used insufficiently. Retailers need not just separate digital solutions, but complex digitalization, which requires changes in organizational structure and business-processes. Only building of general and systematic digital strategy that takes into account organizational transformation, modernization, upgrading quality, optimization of delivery chains, etc. can help retailers raise their competitiveness.